2019
DOI: 10.1021/jacs.9b05072
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Intrinsically Low Thermal Conductivity in Talnakhite Cu17.6Fe17.6S32 Thermoelectric Material: Correlations between Lattice Dynamics and Thermal Transport

Abstract: Understanding the nature of phonon transport in solids and the underlying mechanism linking lattice dynamics and thermal conductivity is important in many fields, including the development of efficient thermoelectric materials where a low lattice thermal conductivity is required. Herein, we choose the pair of synthetic chalcopyrite CuFeS2 and talnakhite Cu17.6Fe17.6S32 compounds, which possess the same elements and very similar crystal structures but very different phonon transport, as contrasting examples to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 59 publications
(97 citation statements)
references
References 61 publications
5
91
0
1
Order By: Relevance
“…Others [9,[73][74][75]78] attribute the boson peak to the strong coupling between acoustic phonons and low-frequency optic phonons, which has been observed in BaAg 2 SnSe 4 , [9] Cd 2 ReO 7 , [78] and CuFeS 2 . [81] For instance, in BaAg 2 SnSe 4 , [9] the vibrations of the AgSe cluster act as two Einstein oscillators in the Debye host. This leads to an ultralow thermal conductivity in BaAg 2 SnSe 4 .…”
Section: Underlying Mechanisms For Thermal Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…Others [9,[73][74][75]78] attribute the boson peak to the strong coupling between acoustic phonons and low-frequency optic phonons, which has been observed in BaAg 2 SnSe 4 , [9] Cd 2 ReO 7 , [78] and CuFeS 2 . [81] For instance, in BaAg 2 SnSe 4 , [9] the vibrations of the AgSe cluster act as two Einstein oscillators in the Debye host. This leads to an ultralow thermal conductivity in BaAg 2 SnSe 4 .…”
Section: Underlying Mechanisms For Thermal Transportmentioning
confidence: 99%
“…In this study, Umklapp scattering, grain boundary scattering, point defect scattering, and phonon resonance scattering are included. Taking these processes as substantially independent, the relaxation rate is [81,86,87]…”
Section: (10 Of 13)mentioning
confidence: 99%
“…Building upon this, several ternary and quaternary compounds with complex structures and incorporating heavy elements have been identied that have lower k l values compared to the industry standard Bi 2 Te 3 . [6][7][8][9][10] Such complex structures oen also have higher effective masses and thus high Seebeck coefficients.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 6 plots the κ L values for typical Cu-based sulfides. [15,21,29,[39][40][41][42][43] It can be seen that Cu 9 Fe 9 S 16 has relatively low κ L even comparing with those compounds including heavy Sb and Sn elements. Most recently, Xie et al found that Cu 17.6 Fe 17.6 S 32 also has intrinsically low κ L as compared with CuFeS 2 , which has the same component elements.…”
Section: Thermoelectric Propertiesmentioning
confidence: 97%
“…Cu-Fe-S-based compounds, including CuFeS 2 , [18] Cu 5 FeS 4 , [20] CuFe 2 S 3 , [19] Cu 17.6 Fe 17.6 S 32 , [21] and Cu 9 Fe 9 S 16 , [22,27,28] gain the interest from TE community because all the consisting elements, Cu, Fe, and S, are non-toxic and earth-abundant. These Cu-Fe-S-based TE compounds are also natural minerals that cated Cu 9 Fe 9 S 16 has a natural nanostructure.…”
Section: Introductionmentioning
confidence: 99%